2018
DOI: 10.1002/anie.201809410
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Amphiphiles Induce Macromolecule Denaturation and Organelle Decomposition in Pathogenic Yeast

Abstract: Cationic amphiphiles are alarge and diverse class of antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…[32][33][34][35][36][37][38] Thed esign of these antimicrobial agents is based on the attachment of membrane-anchoring hydrophobic residues to an aminoglycoside scaffold that is positively charged under physiological conditions.Antibiotics from the aminoglycoside class perturb the fidelity of bacterial translation by binding to the decoding A-site region of the bacterial ribosome;h owever, their target site is shifted from the ribosome to the plasma membrane through conjugation to one or more hydrophobic residues. [42] We observed that these antimicrobials rapidly accumulate in the cytosol causing the denaturation of macromolecules as well as organelle-membrane disruption (Figure 1B). [39][40][41] We recently synthesized inherently fluorescent antifungal cationic amphiphiles to study their effects on Candida yeast cells.…”
Section: Targeting the Plasma Membranementioning
confidence: 92%
See 1 more Smart Citation
“…[32][33][34][35][36][37][38] Thed esign of these antimicrobial agents is based on the attachment of membrane-anchoring hydrophobic residues to an aminoglycoside scaffold that is positively charged under physiological conditions.Antibiotics from the aminoglycoside class perturb the fidelity of bacterial translation by binding to the decoding A-site region of the bacterial ribosome;h owever, their target site is shifted from the ribosome to the plasma membrane through conjugation to one or more hydrophobic residues. [42] We observed that these antimicrobials rapidly accumulate in the cytosol causing the denaturation of macromolecules as well as organelle-membrane disruption (Figure 1B). [39][40][41] We recently synthesized inherently fluorescent antifungal cationic amphiphiles to study their effects on Candida yeast cells.…”
Section: Targeting the Plasma Membranementioning
confidence: 92%
“…We recently synthesized inherently fluorescent antifungal cationic amphiphiles to study their effects on Candida yeast cells . We observed that these antimicrobials rapidly accumulate in the cytosol causing the denaturation of macromolecules as well as organelle‐membrane disruption (Figure B).…”
Section: Selective Targeting Of Subcellular Compartmentsmentioning
confidence: 99%
“…AKs are known to show their antimicrobial activity by increasing the membrane permeability of microorganisms [17,18,19,20,21]. Fluorogenic dyes, such as SYTOX TM green and propidium iodide (PI), are commonly employed for the study of membrane permeabilization (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that cationic amphiphiles are vectors for gene transfection [1,2] and antimicrobial agents [3,4]. Recently, great attention has been paid to the development of positively charged particles, as new targeted delivery systems with improved stability, selectivity, and other properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Surface tension isotherms of surfactant solutions of Triton-X-100 (1, 2), SDS (3, 4), CTAB (5, 6), mono-CS-16(7,8), mono-CS-12 (9, 10), di-CS-16(11,12) in the absence(1,3,5,7,9,11) and presence(2,4,6,8,10,12) of furazolidone, 25°С.…”
mentioning
confidence: 99%